Problems Faced by Cancer Patients due to COVID 19 at Tertiary Cancer Hospital, Chitwan, Nepal - Sushila Koirala; Sabina Giri (Journal of Balkumari College, 2023)
Background: The corona virus disease (COVID 19) Pandemic has had a global impact on health care. Patients with cancer have been affected by the COVID 19 Pandemic and faced various psychosocial problems. Materials and Methods: A descriptive cross-sectional study on title “Problems Faced by Cancer Patients due to COVID 19 at Tertiary Cancer Hospital, Chitwan, Nepal” was conducted at B.P. Koirala Memorial Cancer Hospital, Chitwan to assess problems faced by cancer patients. Non- probability purposive sampling technique was used to select the sample and sample size was 50. Data was collected by using structured interview schedule and distress thermometer. Findings: In this research 50 respondents were included for the study. Among them 72% respondents faced treatment related problems where 27.7% respondents faced unavailability of chemo medicine, nearly half of respondents (48%) faced the transportation related problems and unavailability of transportation service was the key transportation problems faced by 58.3% respondents. Similarly, nearly half of the (46%) faced the accommodation problems and more than two fifth (42%) had economic related problems during COVID 19 pandemic situation. Conclusion: Cancer patients have faced several problems during COVID 19 pandemic such as unavailability of chemo medicine, treatment delay, lack of transportation services, accommodation problem, financial problems and psychological distress. So, cancer hospital should make strategic planning of health care services by means of alternative solutions like telemedicine, home-based palliative care services, and ensuring the availability of essential cancer drugs.